Pemberdayaan Tokoh Agama dalam Pengendalian Hipertensi di Kota Tasikmalaya - Yanyan Bahtiar; Dudi Hartono; Ridwan Kustiawan; Peni Cahyati (Universitas Baiturrahim, 2026)
Hypertension is a major health problem with a high prevalence in Indonesia. The role of religious leaders as agents of community change is considered strategic in disseminating health information, particularly regarding the prevention and control of hypertension. This community service activity aims to improve the knowledge and skills of religious leaders regarding hypertension risk factors, hypertension management, and Islamic spiritual therapy, Spiritual Emotional Freedom Technique (SEFT). The implementation method included health education and SEFT training for 25 religious leaders at the Ummulquro Islamic Community Service Center (DKM) in Tasikmalaya City. The evaluation results showed a significant increase in knowledge about the risks of hypertension (from an average of 46.40 to 66.00; p<0.05), knowledge of hypertension management (43.60 to 64.80; p<0.05), and SEFT skills (22.00 to 62.80; p<0.05). The integration of medical theory in hypertension control with Islamic values, is reflected in the message of the Prophet Muhammad SAW about eating moderately, exercising diligently, and being patient in managing emotions. Spiritual-based health education effectively increases the capacity of religious leaders as health promoters. After participating in this community service, religious leaders can integrate health messages into religious sermons in the community.